Gastro-emotivism: How MasterChef Israel produces therapeutic collective belongings. (October 2021) - Grosglik, Rafi; Lerner, Julia
Although there is burgeoning research on the impact of therapeutic culture in the construction of the individual Self, the ways in which emotional discourse and therapeutic style shape the collective Self have been overlooked. Focusing on the popular reality-television cooking show MasterChef Israel, this article explores the emergence of gastro-emotivism – an interlacing of food with emotions and therapy and a materialization of emotions in the form of food. In MasterChef Israel, gastro-emotivism is used to articulate emotional-therapeutic selves as well as collective belongings and social categories. While recent literature understood the appearance of therapeutic culture in popular media as geared to reshape the individual neoliberal Self, we suggest that gastro-emotivism indicates the expansion of the emotional therapeutic framework in the depiction and construction of collective identities and identifications. We elaborate on the global phenomena of gastro-emotivism and explain its particular Israeli appearance. Emerging from this account is the proliferation of emotional-therapeutic discourse in the Israeli public sphere and its predominance in the ways in which Israelis 'cook, taste and feel' their collective affiliations.